The art of game design a book of lenses - Schell, Jesse (Amsterdam ; Boston : Elsevier/Morgan Kaufmann, 2008)
Anyone can master the fundamentals of game design - no technological expertise is necessary. The Art of Game Design: A Book of Lenses shows that the same basic principles of psychology that work for board games, card games and athletic games also are the keys to making top-quality videogames. Good game design happens when you view your game from many different perspectives, or lenses. While touring through the unusual territory that is game design, this book gives the reader one hundred of these lenses - one hundred sets of insightful questions to ask yourself that will help make your game better. These lenses are gathered from fields as diverse as psychology, architecture, music, visual design, film, software engineering, theme park design, mathematics, writing, puzzle design, and anthropology. Anyone who reads this book will be inspired to become a better game designer - and will understand how to do it. * Jesse Schell is a highly recognizable name within the game industry - he is the former chair of the International Game Developer's Association, and has designed many successful games, including Disney's award-winning Toontown Online. * The book's design methodology was developed at Carnegie Mellon University's Entertainment Technology Center, co-founded by Dr. Randy Pausch of "Last Lecture" fame. * 100 'lenses' are scattered throughout the book. These are boxed sets of questions, each a different way of seeing a game that will inspire the creative process. * 500 pages of detailed, practical instruction on creating world-class games that will be played again and again. * Winner of Game Developer's 2008 Front Line Award in the book category.
In the beginning, there is the designer -- The designer creates an experience -- The experience rises out of a game -- The game consists of elements -- The elements support a theme -- The game begins with an idea -- The game improves through iteration -- The game is made for a player -- The experience is in the player's mind -- Some elements are game mechanics -- Game mechanics must be in balance -- Game mechanics support puzzles -- Players play games through an interface -- Experiences can be judged by their interest curves -- One kind of experience is the story -- Story and game structures can be artfully merged with indirect control -- Stories and games take place in worlds -- Worlds contain characters -- Worlds contain spaces -- The look and feel of a world is defined by its aesthetics -- Some games are played with other players -- Other players sometimes form communities -- The designer usually works with a team -- The team sometimes communicates through documents -- Good games are created through playtesting -- The team builds a game with technology -- Your game will probably have a client -- The designer gives the client a pitch -- The designer and client want the game to make a profit -- Games transform their players -- Designers have certain responsibilities -- Each designer has a motivation -- Goodbye.
Includes bibliographical references (p. 477-479) and index.
Keywords: Computer games -- Design; Jeux d'ordinateur -- Conception; Electronic books